The mutilated Gothic heroine: The figure of Clea in Lawrence Durrell's The Alexandria Quartet. (1st September 2016) - Kreuiter, Allyson
ABSTRACT: The Gothic heroine is generally depicted as innocent, morally blameless, beautiful and often blonde. Threatened by a powerful and villainous male figure, she is enclosed in a confining space, whether a house, a castle or an abbey. In Lawrence Durrell's The Alexandria quartet, the character Clea is portrayed as just such a Gothic heroine. Like any good heroine, Clea is threatened by the powerful and evil desire of a Gothic villain whose death seemingly results in his spectral and vengeful return from the dead into the world of the living. Through a close textual reading of the Quartet, I shall examine how Clea's transgression of her role as blameless, doll-like heroine results in the forcible fragmentation of her body and her reconstruction as a mutilated and prosthetic Gothic other.